2021
DOI: 10.1111/jfpp.15355
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat and γ‐irradiation on fungal load, pasting, and rheological characteristics of three whole and dehulled millets during storage

Abstract: Generally, heat and γ‐irradiation techniques are used in the preservation of millets. Therefore, the effect of heat (150°C to 170°C for 90 s at 300 rpm) and γ‐irradiation (1 kGy and 2.50 kGy) on fungal load, pasting, and rheological characteristics of three whole and dehulled millets (sorghum, foxtail millet, and pearl millet) was investigated during storage (90 days). The findings showed that the pasting (e.g., pasting temperature, peak viscosity, and peak temperature, etc.) and rheological (e.g., storage mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…These results may be explained by the fact that reorganization of starch molecules and degradation of the molecular structure in the millet samples. Similarly, a study reported the decreased pasting temperature when whole and dehulled millets sorghum, pearl, finger millet samples were treated with heat and γ-irradiation (Huang et al., 2021). A study demonstrated the decreased pasting temperature with increased γ-irradiation dose (1 to 5 kGy with an increment of 0.40 kGy/h) for the bean and potato starches (Polesi et al., 2016).…”
Section: Resultsmentioning
confidence: 99%
“…These results may be explained by the fact that reorganization of starch molecules and degradation of the molecular structure in the millet samples. Similarly, a study reported the decreased pasting temperature when whole and dehulled millets sorghum, pearl, finger millet samples were treated with heat and γ-irradiation (Huang et al., 2021). A study demonstrated the decreased pasting temperature with increased γ-irradiation dose (1 to 5 kGy with an increment of 0.40 kGy/h) for the bean and potato starches (Polesi et al., 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The increased radiation exposure results in a reduction in the relative crystallinity of the starch. It is seen as a promising food processing technology with the potential to replace chemical and enzymatic procedures employed on a large scale for starch modification since it doesn't need the addition of chemical reagents and is simple to use without additional equipment [ [113] , [114] , [115] , [116] ].…”
Section: Modification Approaches For Millet Starchmentioning
confidence: 99%
“…At 0.50 kGy, there was no effective minimization of the fungal count, and at 0.75 kGy or above, γ‐irradiation doses diminish the growth of fungal microbes. As a result, the study recommended IR as a safe postharvesting technique in the whole and dehulled millet area (Huang et al, 2021).…”
Section: Millets Based Technologiesmentioning
confidence: 99%